Colonic transendoscopic enteral tubing is revolutionizing intestinal therapeutics, diagnosis, and microbiome research - Zheyu Wang; Xia Wu; Yaxue Wang; Quan Wen; Bota Cui; Faming Zhang (Therapeutic Advances in Gastroenterology)
The intestine, as a crucial organ of the human body, has remained enigmatic despite the remarkable advancements in modern medical technology. Over the past decades, the invention of endoscopic technology has made the noninvasive intervention of the intestine a reality, expanding diagnostic and therapeutic options for diseases. However, due to the single-treatment feature of endoscopic procedures, continuous or repeated medication administration, sampling, and decompression drainage within the intestine have yet to be fulfilled. These limitations persisted until the invention of colonic transendoscopic enteral tubing (TET) in 2014, which realized repeated fecal microbiota transplantation, medication administration, and decompression drainage for the treatment of colon perforation and intestinal obstruction, as well as in situ dynamic sampling. These breakthroughs have not gone unnoticed, gaining global attention and recommendations from guidelines and consensuses. TET has emerged as a novel microbial research tool that offers new paradigms for human microbiome research. This review aims to update the research progress based on TET.